2012
DOI: 10.1007/s00428-012-1345-5
|View full text |Cite
|
Sign up to set email alerts
|

PDCD4/miR-21 dysregulation in inflammatory bowel disease-associated carcinogenesis

Abstract: Inflammatory bowel diseases (IBDs; both ulcerative colitis [UC] and Crohn's colitis [CC]) are well-established predisposing pathological conditions for colorectal cancer (CRC) development. In IBDs, both the endoscopy and the histology assessment of CRC precursors (i.e., dysplasia, also defined as intraepithelial neoplasia) are associated with low interobserver consistency, and no reliable dysplasia-specific biomarker is available. The programmed cell death 4 (PDCD4) tumor suppressor gene is involved in sporadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 41 publications
4
53
0
Order By: Relevance
“…miR-21 has been shown to be upregulated in patients with Crohn's disease and ulcerative colitis (41). Moreover, miR-21 and miR-181b expression levels are increased in colorectal cancer, and expression levels have been linked to a poor prognosis in an American cohort (42).…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 has been shown to be upregulated in patients with Crohn's disease and ulcerative colitis (41). Moreover, miR-21 and miR-181b expression levels are increased in colorectal cancer, and expression levels have been linked to a poor prognosis in an American cohort (42).…”
Section: Discussionmentioning
confidence: 99%
“…PDCD4/miR-21 was often un-balance in precancerous changes or intraepithelial neoplasias of mucosa in IBD. miR-21 increases but PDCD4 decreases may indicate they could be biomarkers of IBD canceration [133]. miRNAs increases significantly in mucosa of IBD by micro-array analysis and real-time polymerase chain reaction [134].…”
Section: Markers Related To Neoplastic Transformationmentioning
confidence: 99%
“…Ludwig et al [73] showed up-regulated level of miR-21 in IBD-associated dysplastic lesions compared to active IBD patients, which was inversely correlated with the expression of PDCD4, a newly characterized tumor suppressor gene. Olaru et al [74,75] found expressions of miR-224 and miR-31 increased successively at each stage of IBD progression from non-inflamed to inflamed non-neoplastic, dysplastic and finally cancerous mucosae.…”
Section: Mirnas Association With Ibd Carcinogenesismentioning
confidence: 99%